Effectiveness of Compassion-Focused Therapy in Depression, Anxiety, Stress, and Physical Symptoms in Patients With Irritable Bowel Syndrome - Kamyar Kaveh; Maryam Kalhornia Golkar; Ali Sahebi (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Irritable bowel syndrome (IBS) is the most common disorder of the digestive system. Despite the long period of study on the treatment of IBS, only a small number of treatments have proven effective. Objectives: The current study aimed to determine the efficacy of compassion-focused therapy (CFT) in depression, anxiety, stress, and physical symptoms in patients with IBS. Methods: This was a quasi-experimental study with a pretest, posttest, follow-up, and control group. The present study was carried out on a total of 30 patients with IBS (diagnosed by a gastroenterologist applying the Rome III criteria) selected and divided into CFT (n=15) and control (n=15) groups. The experimental group received eight sessions of CFT. All groups responded to the Severity of Symptoms of Irritable Bowel Syndrome, and Depression Anxiety Stress Scale-42 was administered as pre-post and follow-up tests. Results: The results showed significantly lower mean scores in depression, anxiety, stress, and physical symptoms in the experimental group in the posttest. The follow-up test given 8 weeks after the posttest did not show any change in the results. Conclusion: The obtained findings support the efficacy of CFT in depression, anxiety, stress, and physical symptoms in patients with IBS.